REDEFINING IDENTITY: THE INTERNATIONAL SCHOOL LANGUAGE TEACHERS’ NARRATIVES OF THE PAST AND PRESENT ENTERPRISE - Swanti, Veronika (International Journal of Indonesian Education and Teaching (IJIET), 2020)
Researchers have been studying pre-service and in-service language teacher identity for more than two decades across countries. However, there is few research conducted in Indonesia regarding in-service language teacher identity in an international school. The present study aims at investigating international school language teachers’ prior experience and current teaching enterprise in redefining their professional and personal identity. The study employs qualitative method embracing questionnaire and in-depth interviews. There are 6 participants including teachers of Indonesian, English, Chinese, French, and Spanish language subjects. This study found that language teachers at AHS perceived their professional identity through the production of metaphors and the recalling of past and present teaching enterprise. Further exploration on the language teacher identity construction in Indonesia is then needed.DOI: 10.24071/ijiet.2020.040110